2023
DOI: 10.1002/anie.202302400
|View full text |Cite
|
Sign up to set email alerts
|

Inside Cover: Ultra‐fast One‐Handed Helix Induction and Its Static Helicity Memory in a Poly(biphenylylacetylene) with a Catalytic Amount of Chiral Ammonium Salts (Angew. Chem. Int. Ed. 15/2023)

Abstract: Catalytic ultra‐fast helix induction and its static helicity memory in a poly(biphenylylacetylene) were achieved by using chiral ammonium salts, as reported by Katsuhiro Maeda, Eiji Yashima, and co‐workers in their Research Article (e202217020). The remarkable acceleration of the helix‐induction rate accompanied by strong chiral amplification relies on crown‐ether‐like specific intermolecular complex formation of the two methoxymethoxy groups of the biphenyl pendants with chiral ammonium species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[14,[36][37] This phenomenon was denoted as "memory effect". [38] They found that this process can be extrapolated to other polyacetylene derivatives, such as poly(biphenylacetylene)s (PBPA) [39][40] and poly(diphenylacetylene)s (PDPAs). [41][42] These systems were recently denoted as first-(PPAs), second-(PBPAs) and third-(PDPAs) generation of static helicity memory respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[14,[36][37] This phenomenon was denoted as "memory effect". [38] They found that this process can be extrapolated to other polyacetylene derivatives, such as poly(biphenylacetylene)s (PBPA) [39][40] and poly(diphenylacetylene)s (PDPAs). [41][42] These systems were recently denoted as first-(PPAs), second-(PBPAs) and third-(PDPAs) generation of static helicity memory respectively.…”
Section: Introductionmentioning
confidence: 99%